THE IMPORTANCE OF MODERN METHODS IN USING THE HERITAGE OF ANCESTORS THROUGH THE SCIENCE OF EDUCATION IN ELEMENTARY GRADES - Siddikova Zulfiya Murod kizi; Madrakhimova Shohista Xikmatillo kizi (Western European Studies, 2024)
The article discusses the importance of modern methods in using the heritage of ancestors through the science of education in primary grades.
Keywords: successful; science; methodical; educational process